Breakneck : China's quest to engineer the future - Wang, Dan (Writer on China) (W. W. Norton & Company, 2025)
"A riveting, firsthand investigation of China's seismic progress, its human costs, and what it means for America. For close to a decade, technology analyst Dan Wang has been living through the country's astonishing, messy progress. China's towering bridges, gleaming railways, and sprawling factories have improved economic outcomes in record time. But rapid change has also sent ripples of pain through the society. This reality -- political repression and astonishing growth -- is not a paradox, but rather a feature of China's engineering mindset. In Breakneck, Wang blends political, economic, and philosophical analysis with reportage to reveal a provocative new framework for understanding China -- one that helps us see America more clearly, too. While China is an engineering state, relentlessly pursuing megaprojects, the United States has stalled. America has transformed into a lawyerly society, reflexively blocking everything, good and bad. Blending razor-sharp analysis with immersive storytelling, Wang offers a gripping portrait of a nation in flux. Breakneck traverses metropolises like Shanghai, Chongqing, and Shenzhen, where the engineering state has created not only dazzling infrastructure but also a sense of optimism. The book also exposes the downsides of social engineering, including the surveillance of ethnic minorities, political suppression, and the traumas of the one-child policy and zero-Covid. In an era of animosity and mistrust, Wang unmasks the shocking similarities between the United States and China. Breakneck reveals how each country points toward a better path for the other: Chinese citizens would be better off if their government could learn to value individual liberties, while Americans would be better off if their government could learn to embrace engineering -- and to produce better outcomes for the many, not just the few." --